2004
DOI: 10.1063/1.1637953
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium storage in nanocrystalline magnesium thin films

Abstract: Nanocrystalline magnesium deuteride thin films with the β-MgD2 structure were prepared by vacuum evaporation of hexagonal magnesium (h-Mg) samples and thermal annealing in 0.15 MPa D2 atmosphere at 373 K. Thermal desorption spectroscopy analysis indicated that the rate-limiting step in the deuterium desorption was given by the thermal decomposition of the deuteride phase. The activation energy Δg of the β-MgD2→h-Mg+D2 reaction scaled from 1.13±0.03 eV in 650-nm-thick films to 1.01±0.02 eV in 75-nm-thick films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
5
24
0
Order By: Relevance
“…The trapping defects can be vacancy-type defects at the interface, e.g., related to the prestage of delamination involving breaking of bonds at the interface, to the diffusion of Pd, creating an intermixed interface area containing vacancies, or to the transformation of the top Pd-Mg layer into Mg 2 Pd which may contain itself positron-trapping defects. Delamination itself does not yet occur at these temperatures, consistent with positron studies on Pd-capped Mg films at the still lower hydrogen sorption temperatures of around 373-390 K. 11 For completeness we note that the full VEPFIT analysis 36 of the positron Doppler curves in Figs. 1, 7, and 8 is consistent with this picture.…”
Section: Depth-resolved Pd-mg Alloying and Initial Stages Of Delasupporting
confidence: 59%
See 2 more Smart Citations
“…The trapping defects can be vacancy-type defects at the interface, e.g., related to the prestage of delamination involving breaking of bonds at the interface, to the diffusion of Pd, creating an intermixed interface area containing vacancies, or to the transformation of the top Pd-Mg layer into Mg 2 Pd which may contain itself positron-trapping defects. Delamination itself does not yet occur at these temperatures, consistent with positron studies on Pd-capped Mg films at the still lower hydrogen sorption temperatures of around 373-390 K. 11 For completeness we note that the full VEPFIT analysis 36 of the positron Doppler curves in Figs. 1, 7, and 8 is consistent with this picture.…”
Section: Depth-resolved Pd-mg Alloying and Initial Stages Of Delasupporting
confidence: 59%
“…XRD showed that this particular film was hydrogenated partially, attaining a MgH 2 phase fraction of ϳ63% ͑ϳ5 wt % hydrogen loading͒. The estimated change in Doppler S-parameter for the complete transformation of Mg to MgH 2 is therefore ⌬S / S ϳ −4.5%, i.e., close to the reduction of ϳ5% reported by Checchetto et al 11 The reduction in the S-parameter stems from a clear broadening in the valence part of the electron momentum density with formation of the metal hydride, as observed in a Compton scattering study on Mg and MgH 2 powders by Garreau and Loupias. 23 The reduction is therefore primarily related to the change in valence electron momentum distributions ͑EMDs͒ of the bulk metal and metal hydride systems, as supported by the calculated momentum distributions of valence electrons in Mg and MgH 2 shown in Fig.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Recent studies on semiconductor NCs [11][12][13][14] and metal hydrides [15][16][17] showed the promise of positron annihilation to aid in solving bottlenecks in these fields. The positron can be used as a sensitive probe for detecting the surface composition of semiconductor NCs and the confinement of the upper valence electron states (Fig.…”
mentioning
confidence: 99%
“…hydriding/dehydriding cycles was also studied by the positron annihilation spectroscopy (PAS) [58]. After the very first decomposition of MgD2 the increase of void-like defects was observed accompanied by the decrease in deuterium storage capacity.…”
Section: Pd-capped Mg Thin Filmsmentioning
confidence: 99%